2021
DOI: 10.12688/hrbopenres.13119.2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors that influence the practice of Open Science by early career health researchers: a mixed methods study

Abstract: Background: There is a growing global movement towards open science and ensuring that health research is more transparent. It is vital that the researchers are adequately prepared for this research environment from early in their careers. However, limited research has been conducted on the barriers and enablers to practicing open science for early career researchers. This study aimed to explore the views, experiences and factors influencing open science practices amongst ECRs working in health research. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
(28 reference statements)
0
23
0
Order By: Relevance
“…Assessment of barriers and enablers to Open Science practices amongst early career researchers working in health research found that cultural and academic pressures, the positives and negatives of increased accountability and transparency, and the need for more training and supporting resources were important facilitators (Zečević et al, 2021). However, the study was small (n=14) and only 35% of…”
Section: Open Science Practices Within Health Psychologymentioning
confidence: 88%
“…Assessment of barriers and enablers to Open Science practices amongst early career researchers working in health research found that cultural and academic pressures, the positives and negatives of increased accountability and transparency, and the need for more training and supporting resources were important facilitators (Zečević et al, 2021). However, the study was small (n=14) and only 35% of…”
Section: Open Science Practices Within Health Psychologymentioning
confidence: 88%
“…Social opportunity, which includes support from social structures and colleagues to engage with Open Research in the context of this study, was the 1 st and 3 rd most requested behaviour change component by respondents to support Open Research. The need for such support from wider social structures to facilitate Open Research has been previously discussed in meta research on preregistration (Osborne & Norris, 2022) and Registered Reports , and is supported by Early Career Researchers (Kowalczyk et al, 2022;Zečević et al, 2021) and Open Research networks such as the UKRN (Stewart et al, 2022). Whilst there has been promising progress to incentivise, recognise and reward Open Research practices, including within journals (e.g., via badges; Kidwell et al, 2016) and across them (e.g., via TOP factor assessment; Nosek et al, 2016), by funders (e.g., Registered Reports funding partnerships; (Clark et al, 2021;Drax et al, 2021), and some institutions (e.g., European Universities Research practices) were seen by academics as support that would most help them to use more Open Research practices.…”
Section: Discussionmentioning
confidence: 99%
“…Antecedents to Open Research behaviours, including associated barriers and enablers, have been investigated with a view to maximising uptake (Osborne & Norris, 2022;Robson et al, 2021;Zečević et al, 2021). Meta-research has identified the extent to which researchers engage with Open Research across different disciplines (Cashin et al, 2021;Christensen et al, 2019;Hardwicke et al, 2021;Norris et al, 2021Wallach et al, 2018).…”
Section: Measures Of Open Researchmentioning
confidence: 99%
“…To examine the second research question, multivariate linear regression in R was used to analyze the impact of the predictor variables (i.e., years of experience, number of publications, career stage, attitudes, methodological focus, perceived norms, and knowledge) on participants' intended future practices. The independent variables of attitudes, knowledge, and perceived norms were derived from the conceptual framework and the experience, number of publications, career stage, and methodological focus variables were derived from recent research examining researchers' perceptions of open science practices (Abele-Brehm et al, 2019;Soderberg et al, 2020;Toribio-Flórez, 2021;Zečević et al, 2020). For the career stage variable, tenured researchers were designated as the reference group, and for the methodological focus variable, group quantitative research was designated as the reference group.…”
Section: Discussionmentioning
confidence: 99%